2018
DOI: 10.1016/j.conbuildmat.2018.07.184
|View full text |Cite
|
Sign up to set email alerts
|

Short sisal fiber reinforced recycled concrete block for one-way precast concrete slabs

Abstract: This work is dedicated to the assessment of the structural capacity of a new lightweight block for one-way precast concrete slabs made of short sisal fiber reinforced concrete (SSFRC) containing natural and recycled aggregate. Flexural tests were carried out on SSFRC block samples, as well as on ceramic and EPS blocks used commercially. Slab panels including SSFRC, ceramic and EPS blocks were tested under four point bending configuration to assess the benefits of the new SSFRC block in quasi-real slab conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…According to one research study, 1.5% of the fibers increased CS by nearly 15% when compared to the control specimens' strength [43]. The addition of SSF to the UHPC mixture, however, enhances the porosity of the matrix [78]. As a result, adding SSF to UHPC has two opposing impacts on CS, and further research is needed to relieve this detrimental impact on UHPC's mechanical strength.…”
Section: Mechanical Strength 41 Compressive Strength (Cs)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to one research study, 1.5% of the fibers increased CS by nearly 15% when compared to the control specimens' strength [43]. The addition of SSF to the UHPC mixture, however, enhances the porosity of the matrix [78]. As a result, adding SSF to UHPC has two opposing impacts on CS, and further research is needed to relieve this detrimental impact on UHPC's mechanical strength.…”
Section: Mechanical Strength 41 Compressive Strength (Cs)mentioning
confidence: 99%
“…The biggest strength gain after 28 days was determined to be 29.15 percent [49]. According to one research study [78], adding 6.0 percent (by mass of binder) SSF with a length of 40 mm to regular cement concrete reduced CS by 22.0 percent. The increased porosity caused by the inclusion of fibers is responsible for the decrease in CS.…”
Section: Mechanical Strength 41 Compressive Strength (Cs)mentioning
confidence: 99%
“…When the fibers content is 1.0%, the mechanical properties of concrete are improved in the initial and later stages [ 104 ]. In another study, the addition of 6.0% sisal fibers of length 40 mm to ordinary concrete resulted in a 22.0% reduction in compressive strength [ 105 ]. Similarly, kenaf fiber-reinforced concrete has better mechanical properties than standard concrete samples.…”
Section: Mechanical Properties Of Pfrgsmentioning
confidence: 99%
“…Mansour et al (2015) found that adding a thin layer of steel fiber concrete into precast concrete slabs could increase its flexural performance. Dal Lago et al ( 2017), Lima et al (2018), and Crocetti et al (2014 used fiber reinforcement in prefabricated concrete slabs and found that it has clear benefits on the post-cracking flexural capacity. May et al (2019) studied the required load-bearing capacity and deflection stiffness of precast slabs made of carbon reinforced concrete at conventional construction height and demonstrated that the slab concrete could be reduced continuously by optimizing the load-bearing structure.…”
Section: Introductionmentioning
confidence: 99%